Sphaeropsis sapinea, with special reference to its occurrence on Pinus spp. in South Africa - Swart, Wijnand J (Stellenbosch : Stellenbosch University, 2012)
Thesis (M.Sc. Agric.) -- University of Stellenbosch, 1986.